1786 N.Y. Laws 220 - (:unkn) unknown (My University, 1786)
An Act to Regulate the Militia, ch. 25: That every citizen so enroled [sic] and notified shall within three months thereafter provide himself at his own expence with a good musket or firelock, a sufficient bayonet and belt[,] a pouch with a box therein to contain not less than twenty four cartridges suited to the bore of his musket or firelock, each cartridge containing a proper quantity of powder and ball, two spare flints, a blanket and knapsack[.]
Keywords: ARMED FORCES